Proceeding of the Bangkok symposium on acid sulfate soils: Second International Symposium on acid sulphate soils, Bangkok, Thailand, January 18-24, 1981 (ILRI, 1982)
The symposium emphasises the managementof soil/water/plant systems under acid sulphate soil conditions in tropical agro-ecological zones in Southeast Asia and West Africa